The Use Of Compost And Phonska Plus On Acid Soil On The Growth And Production Of Pakcoy (Brassica rapa L.) In Minahasa Regency” - Joice M. J. Supit; Yani E. B. Kamagi; Lientje Theffie Karamoy (Jurnal Agroekoteknologi Terapan, 2022)
A pot experiment on “ The Use of Compost and Phonska Plus on acid soil on the growth and production of pakcoy (Brassica rapa L.) in Minahasa Regency”, with specific objectives: a) Increasing the use of acid land for agricultural production activities; b) Determine the optimal dosage of compost and Phonska Plus. c) Improve the physical, chemical and biological properties of soil for acid soils. Giving dolomite as much as 100 g/pot. Compost treatment was K0 : 0 ton/ha as control; (K1) :15 ton/ha ; (K2) :30 tons/ha; (K3):45 ton/ha; and (K4): 60 tons/ha. Phonska Plus treatment is (P0) : 0 kg/ha; (P1) : 400 kg/ha; (P2) : 800 kg/ha ; and (P3) : 1200 kg/ha. Pakcoy plant as an indicator. Factorial experimental method with a completely randomized design (CRD) and 3 replications. Anova and LSD statistical testing. The results of this study show that: 1). The analysis of soil chemical properties on acid soil before liming dolomite, phonska plus and compost fertilizer treatmen showed acidic pH, low organic matter, very low total N, very low available P and low available K; whereas after liming of dolomite, phoska plus and compost showed slightly acidic-neutral pH, medium-high organic matter, very low-low total N, very low-moderate available P, moderately available K. 2). Phonska Plus treatment and compost had a significant effect on the growth and production of Pakcoy. The optimum dose of Phonska Plus (1,200 Kg/ha) and Compost (45 tons/ha) gave the maximum value for plant height, number of leaves, and plant wet weight. Keywords: Compost, Phonska Plus, Acid Land, Pakcoy. Abstrak Percobaan pot tentang “Pemanfaatan Kompos dan Phonska Plus pada lahan masam terhadap pertumbuhan dan produksi sawi pakcoy (Brassica rapa L.) di Kabupaten Minahasa”, dengan tujuan khusus adalah a) Meningkatkan penggunaan lahan masam untuk kegiatan produksi pertanian; b) Menentukan dosis kompos dan Phonska Plus yang optimal. c) Memperbaiki sifat fisik, kimia dan biologi tanah bagi lahan masam. Pemberian dolomite sebanyak 100 gr/pot. Perlakuan kompos yaitu K0 : 0 ton/ha sebagai kontrol; (K1) :15 ton/ha ; (K2) :30 ton/ha; (K3):45 ton/ha; dan (K4): 60 ton/ha. Perlakuan Phonska Plus yaitu (P0) : 0 kg/ha; (P1) : 400 kg/ha; (P2) : 800 kg/ha ; dan (P3) : 1200 kg/ha. Tanaman Sawi Pakcoy sebagai indikator. Metode percobaan faktorial dengan rancangan dasar acak lengkap (RAL) dan 3 ulangan. Pengujian statistik Anova dan BNT. Hasil dari penelitian ini adalah: 1). Sebelum pengapuran dolomite, phonska plus dan kompos menunjukkan pH masam, bahan organik rendah, N total sangat rendah, P tersedia sangat rendah dan K tersedia rendah; sedangkan sesudah pengapuran dolomite, phoska plus dan kompos menunjukkan pH agak masam-netral, bahan organik sedang–tinggi, N total sangat rendah-rendah, P tersedia sangat rendah-sedang, K tersedia sedang. 2). Perlakuan Phonska Plus dan kompos berpengaruh nyata terhadap pertumbuhan dan produksi tanaman Sawi Pakcoy. Dosis optimum Phonska Plus (1.200 Kg/ha) dan Kompos (45 ton/ha) memberikan nilai maksimal terhadap tinggi tanaman, jumlah daun, dan berat basah tanaman. Kata kunci : Kompos, Phonska Plus, Lahan Masam, Sawi Pakcoy